Pengabdian Masyarakat Pengembangan Destinasi Wisata Untuk Meningkatkan Kunjungan Wisatawan Pada Pokdarwis DewiTapa Desa Cirendeu Bandung - Susila, Mochamad Nandi; Sundari, Jenie; Ekawati, Donna; Baidawi, Taufik (Universitas Islam Madura, 2025)
Cirendeu Village, located in Bandung City, is one of the areas with significant cultural and natural tourism potential. One of the active tourism awareness groups (Pokdarwis) in this region is Pokdarwis DewiTapa, which has been managing various attractions based on local culture and environmental conservation. However, the number of tourist visits to this area remains relatively low due to limitations in promotion, digital information, and access to technology that can reach potential visitors more widely. In today’s digital era, the presence of mobile application–based information media is crucial for introducing and facilitating tourist access to destinations. Therefore, this community service activity aims to develop an Android-based mobile tourism application as a digital promotion platform and an interactive visitor guide. The application will provide information on tourist attractions, location maps, cultural event schedules, facilities, and Pokdarwis DewiTapa’s contact services. This activity will also include training for Pokdarwis members on how to use the application, digital content management, and mentoring to ensure the sustainability of the implemented technology. It is expected that through the development of this mobile-based information system, Pokdarwis DewiTapa will be able to expand its promotional reach, increase the number of tourist visits, and strengthen the local community’s capacity in managing technology-based tourism.